Strategies of Combating Corruption in Nigeria: The Islamic Perspective - Usman Sambo; Babayo Sule (UIN Sunan Gunung Djati Bandung, 2021)
Corruption has become a pandemic and a moral burden that bedeviled the world. Corruption is a practice that permeates all societal segments, sectors, activities and it takes various shapes, forms, dimensions, classifications and manifestations. Nearly all countries of the world are affected by the endemic of corruption albeit, in different magnitude with some having lower incidence while others a high rate of occurrence. Corruption has constituted itself as a political and socioeconomic problem worldwide because it leads to misgovernance, deprivation, inequality and squander of scarce public resources which have the concomitant repercussions of poverty, insecurity, joblessness, hunger and malnutrition, poor healthcare services delivery and low quality education. The problem of corruption took a new dimension when it continuously defies various strategies and alternatives proffered by nation-states, international organisations and agencies. One of the outstanding measures that permanently proves workable is the Islamic model which forbids the practice of corruption and ties it with moral burden and spiritual integrity. Hence, this study presented an alternative model with reference to Nigeria as the area of study. The study utilised a conceptual descriptive approach where documented sources were consulted and analysed. The study discovered that despite the existence of various anti-graft agencies, corruption continues in Nigeria unabated which portrays the need for adopting a different approach and that has been provided as the Islamic perspective. The study recommends among several others that the Islamic ethics and morals of detesting corrupt practices and the accompanied sanctions should be integrated in the crusade against corruption.